Neurological Complications in Patients Undergoing Cardiac Surgery: A Tertiary Care Experience - NIAZI, ATTAULLAH KHAN; MAHMOOD, MUHAMMAD MOHSIN; MIKRANI, BENAZEER; SARWER, MUHAMMAD MANSOOR; AKRAM, SIDDIQA; YAQOOB, ZARGHAM (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Morbidity related to neurology complications continues to be a major issue after cardiac surgery. Postoperative stroke and delirium contribute to prolonged hospital ICU stay and increase in cost as well. Methods: Prospective observational study conducted at Mayo Hospital Lahore in Cardiac surgery Department from July 2024 to June 2025. A total of 210 adult patients undergoing cardiac surgery participated in the research. Demographic factors, comorbidity, variables of surgery and neurological outcomes were examined. The patterns of occurrence of the neurological complications by the type of procedure and high-risk groups were assessed. Predictors of postoperative neurological complications were identified by using multi-variable analysis. Results: The risk of neurological complications depended on the complexity of the procedures performed with high incidence of strokes being reported in Mitral and Aortic valvular surgeries and in both CABG + valvular surgeries in comparison to isolated Coronary Artery Bypass Grafting CABG. Postoperative delirium was strongly predictable by advanced age, high scores in surgical risk, previous cerebrovascular pathology, and a decrease in cerebral oxygen saturation. Conclusion: Multi-factorial neurological complications after Cardiac Surgery procedures are dependent and affected by patient factors, the complexity of procedures and physiological events. Early risk factors evaluation and perioperative management in cardiac surgery should be optimised to enhance the neurological outcome.